2013: I Materiali di Sutura in Urologia. Issue 3 (July 2013) - Fiori, Cristian; Amparore, Daniele; Checcucci, Enrico; Aimar, Roberta; Scarpa, Roberto Mario; Porpiglia, Francesco
Since ancient times, sutures have been a fundamental part of the surgeon's practice. Beside the vegetable and animal origin materials, in the last decades different refined synthetic materials have been introduced in the clinical practice. More recently, different devices, such as staplers and tissue sealers have been developed. Thus, more than ever, urologists are faced with a multitude of suture materials, and research of safe, effective materials and devices seems to be continuously growing. The introduction and widespread diffusion of laparoscopic and robotic surgery has further boosted this research. Given there is no single material that is ideal for all situations, the surgeon must choose the best material for each particular case. The aim of this non-systematic review is to summarize the more innovative suture materials and devices and to describe the different surgical methods to utilize them both in general and in urologic surgery.